OPTIMALISASI PERAN KADER KESEHATAN DALAM MEMFASILITASI LAHIRNYA GENERASI TERBAIK “BAYI M.ASI.Eks.,” PADA IBU BEKERJA - Fitra Duhita; Nofrida Pratistiyana; Nurul Aini (Pengabdian dan Pengembangan Masyarakat Sekolah Vokasi UGM, 2021)
The Sakernas Data at 2015 and 2017 of Kulon Progo Regency showed that there is an increase in women's labor force participation rates by two percent (96% to 98%). The increase in these number for women will continue to occur along with the increase in the level of education and the scope of employment that is increasingly varied. The opening of a new airfield in Kulon Progo also indirectly expands employment opportunities with all the consequences, including the possibility of increasing labor force participation rates for women. Responding to this paradigm shift, the participation of all parties, specifically in this activity is a cadre, is expected to have more adequate abilities in assisting every woman to continue to provide the best nutrition as the right of every child, even as a working mother. It is expected that the optimum breastfeeding will reach exclusive breastfeeding, and continue until 2 years. The choice of place is based on the real contribution of the Vocational School especially the Department of Health Services and Information to the environment around the teaching industry area. The activity carried out was Optimizing the Role of Health Cadres in Facilitating the Birth of the Best Generation